PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN PEMBELAJARAN BIOLOGI MATERI SISTEM PENCERNAAN PADA MANUSIA SMA KRISTEN SONDER - Tesalonika Monding; Anatje Lihiang; Carolin Manuahe (SOSCIED, 2023)
Make a Match is a learning model that invites students to find answers to a question or a pair of concepts through a pair card game within a specified time limit. This research aims to improve student learning outcomes in Biology subjects in class XI MIPA SMA Kristen Sonder by using the Make a Match type learning model. This Class Action Assessment is carried out in two cycles consisting of planning, implementation, observation and reflection stages. The results of the research showed that in cycle I the average value was 72.2 and continued with cycle II, the average value was 83.3. In this way, there is an increase, so that the criteria for learning completeness increases. The conclusion shows that the application of the Make a Match type cooperative learning model can improve student learning outcomes in Biology lessons on the Digestive System in Humans.